MILITARY AIR FORCES OF THE REPUBLIC OF UZBEKISTAN: YESTERDAY AND TODAY - Khasiyat Normuminovna Makhmanova (Ecominds Press, 2025)
This article analyzes the organization of the Air Force of the Republic of Uzbekistan, the stages of its development, the reforms carried out, and their results. The article is significant because it is written based on archival documents, periodical press materials, and scientific research materials, drawing on new information.
Keywords: Air Force, airfield, aeroclub, aviation school, aviation fuel, flight hours.